Clinical and microbiological characteristics of thoracic empyema: retrospective analysis in a tertiary care centre - Karmakar, Saurabh; Karmakar, Shilpi; Prasad, Rajendra; Kant, Surya; Nath, Alok; Mahdi, Farzana (International Journal of Advances in Medicine, 2017)
Background: Clinicians should monitor characteristics of empyema to improve clinical decision making. The objective of this study was to evaluate the clinical and microbiological characteristics of patients of thoracic empyema in a tertiary hospital. Methods: From 01 January 2016 to 31 December 2016, 110 patients with thoracic empyema were treated. An analysis of organisms cultured from empyema fluid and their antibiotic sensitivity patterns was done. The organism isolated from the pleural fluid, were classified into four groups: gram positive; gram negative; acid fast bacilli (AFB) and fungal. Observational, retrospective chart review design study conducted in Department of Pulmonary Medicine, Era’s Lucknow Medical College and Hospital, a tertiary level health care centre. Results: Cultures yielded 136 isolates from 96 patients (90.66%) whereas samples from 14 patients (09.34%) were sterile. The isolates were classified as gram positive (20), gram negative (110), AFB (4), fungal (2) and sterile (14). Gram negative bacteria were the most common organism. The prevalence of multi drug resistant Pseudomonas aeruginosa was 12%. 50% of all Staphylococcus aureus were Methicillin resistant. Conclusions: There is high prevalence of gram-negative bacilli and the high rates of isolation of multi drug resistant Pseudomonas aeruginosa and Methicillin resistant Staphylococus aureus in empyema. This indicates a need for judicial use of antibiotics at the referring centres and more aggressive antibiotic therapy at the referral centres. The practise of empirical broad spectrum antibiotic treatment of empyema must be reviewed.